Saint George and the dragon : a golden legend - Hodges, Margaret; Hyman, Trina Schart; Spenser, Edmund, 1552?-1599. (Boston : Little, Brown, 1984)
Retells the segment from Spenser's The Faerie Queene, in which George, the Red Cross Knight, slays the dreadful dragon that has been terrorizing the countryside for years and brings peace and joy to the land.
Children's Catalog (Wilson)
4.0
Keywords: George, -- Saint, -- d. 303 -- Legends; George, -- Saint, -- d. 303.; Folklore -- England; Caldecott 1985 Medal Winner; Knights and knighthood -- Folklore; Dragons -- Folklore